The Jaiminīya Mahābhārata Mairāvaṇacaritam & Sahasramukharāvaṇacaritam: A Critical Edition with English Translation from the Grantha Script, by Pradip Bhattacharya and Shekhar Kumar Sen. (1st August 2018) - Brockington, John
Abstract : The Jaiminīya Mahābhārata Mairāvaṇacaritam & Sahasramukharāvaṇacaritam: A Critical Edition with English Translation from the Grantha Script, by Pradip Bhattacharya and Shekhar Kumar Sen. New Delhi: National Mission for Manuscripts and New Bharatiya Book Corporation, 2017. 2 vols., lvii + 747 pp., Rs. 1000 (hb). ISBN 978-9-380-82902-9 and 978-9-380-82948-7.